Effects of sodium intake on postural lightheadedness: Results from the DASH‐sodium trial. Issue 3 (28th January 2019) - Peng, Allison W.; Appel, Lawrence J.; Mueller, Noel T.; Tang, Olive; Miller, Edgar R.; Juraschek, Stephen P.
Abstract : Lightheadedness after standing contributes to adverse clinical events, including falls. Recommendations for higher sodium intake to treat postural lightheadedness have not been evaluated in a trial setting. The Dietary Approaches to Stop Hypertension (DASH)‐Sodium trial (1998‐1999) tested the effects of the DASH diet and sodium reduction on blood pressure (BP). Participants were randomly assigned to DASH or a typical Western diet (control). During either diet, participants ate three sodium levels (50, 100, 150 meq/d at 2100 kcal) in random order for 30‐days, separated by 5‐day breaks. Participants reported the presence and severity of postural lightheadedness at baseline and after each feeding period. There were 412 participants (mean age 48 years; 57% women; 57% black). Mean baseline SBP/DBP was 135/86 mm Hg; 9.5% reported baseline lightheadedness. Among those consuming the DASH diet, high vs low sodium increased lightheadedness (OR 1.71; 95% CI: 1.01, 2.90; P = 0.047) and severity of lightheadedness ( P = 0.02), but did not affect lightheadedness in those consuming the control diet (OR 0.77; 95% CI: 0.46, 1.29; P = 0.32). Among those consuming high vs low sodium in the context of the DASH diet, adults <60 vs ≥60 years old experienced more lightheadedness ( P ‐interaction = 0.04), along with obese vs non‐obese adults ( P ‐interaction = 0.01). In the context of the DASH diet, higher sodium intake was associated with more frequent and severe lightheadedness. These findings challenge traditional recommendations to increase sodium intake to prevent lightheadedness.